Accuracy of Ultrasonography in Diagnosis of Shoulder Dislocation: A Systematic Review - Entezari, Pouya (Adv J Emerg Med, 2019)
CONTEXT: This systematic review of clinical trials was conducted to compare the diagnostic accuracy of ultrasound in comparison to plain radiography in shoulder dislocation. EVIDENCE ACQUISITION: MEDLINE, Cochrane Database of Systematic Reviews, clinicaltrials.gov, Google scholar, and Scopus were searched for clinical trials. Diagnosis of shoulder dislocation and confirmation of shoulder reduction were the outcomes of interest. Sensitivity, specificity, positive predictive value and negative predictive value of included clinical trials were calculated. RESULTS: Seven studies met our inclusion criteria and were analyzed. All included studies except two had a sensitivity and specificity of 100% for ultrasound (one with a sensitivity of 54% and one with a specificity of 60%). CONCLUSION: It can be suggested that ultrasound can be used as a reliable alternative diagnostic method for detection of both dislocation and reduction in shoulder joint. This may decrease the delay in treatment, cost, radiation exposure, and need for repeated sedation.